Local Wisdom in the Picture Storybook for Elementary School Students in Sukoharjo Regency - Veronika Unun Pratiwi; Sarwiji Suwandi (Budapest International Research and Critics University, 2021)
In teaching Indonesian language, the unification between language and culture is a really interesting source of study. The objectives of this study is to explore the identity of Gatotkaca character values of local wisdom found in the elementary school students’ reading book in several elementary schools in Sukoharjo Regency. This study was designed with a qualitative descriptive research model with content analysis technique. The data and data sources were taken from an elementary school student's reading book Gatotkaca Satria from Pringgodani. The results revealed that the local wisdom indicators primarily found in the reading book of Gatotkaca Satria Pringgodani including values of patriotism and other values such as discipline, hard work, creativity, sovereignty, democracy, respect for achievement, companionship, peace-loving, love of reading, and care to environment, social security, and responsibility. Gatotkaca principally showed the attitudes that can motivate students to develop patriotic sense.